Quality management and safety performance: the influence of ethical leaders among public sector employees - Birasnav, M.; Dahiya, Rinki; Dalpati, Avadhesh (The TQM Journal, 2026)
Keywords: Ethical leadership; Incentive; Job satisfaction; Motivation for QM implementation; Perceived safety performance; Public sector; Quality (philosophy); Structural equation modeling; Survey data collection; Test (biology); Work (physics); dept.mgt

Integrating Theories of Strategic Leadership, Social Exchange, and Structural Capital in the Context of Buyer–Supplier Relationship: An Empirical Study - Birasnav, M.; Mittal, Rakesh; Dalpati, Avadhesh (Global Journal of Flexible Systems Management, 2019)
This study is aimed at improving the purchasing cycle time in a buyer–supplier relationship by integrating the facets of strategic leadership, social exchange, and social capital theories. We developed and tested a conceptual model that postulated relationships among strategic leadership behavior, relational trust and commitment, structural capital, and purchasing cycle time. Data were collected from purchase managers and their employees working in 105 manufacturing companies and analyzed using structural equation modeling technique. Our findings indicated that strategic leadership behaviors are positively related to trust in the buyer–supplier relationship. In addition, trust enhances relational commitment between buyer and supplier, which in turn positively relates to information sharing and supplier development. Further, increased information sharing in the relationship results in reduced purchasing cycle time. Implications for both theory and practice are discussed in depth, and directions for future research are suggested.
Keywords: Cycle time; Information sharing; Relational commitment; Relational trust-Strategic leadership; Supplier development; dept.mgt; peer-reviewed